Influence of Higher Modes on Strength and Ductility Demands of Soil–Structure Systems - Ganjavi, B.; Hao, Hong; Hajirasouliha, I. (World Scientific Publishing, 2016)
Due to the inherent complexity, the common approach in analyzing nonlinear response of structures with soil–structure interaction (SSI) in current seismic provisions is based on equivalent Single Degree-of-Freedom systems (E-SDOF). This paper aims to study the influence of higher modes on the seismic response of SSI systems by performing intensive parametric analyses on more than 6400 linear and non-linear Multi Degree-of-Freedom (MDOF) and E-SDOF systems subjected to 21 earthquake records. An established soil-shallow foundation-structure model with equivalent linear soil behavior and nonlinear superstructure has been utilized using the concept of cone models. The lateral strength and ductility demands of MDOF soil–structure systems with different number of stories, structure-to-soil stiffness ratio, aspect ratio and level of inelasticity are compared to those of E-SDOF systems. The results indicate that using the common E-SDOF soil–structure systems for estimating the strength and ductility demands of medium and slender MDOF structures can lead to very un-conservative results when SSI effect is significant. This implies the significance of higher mode effects for soil–structure systems in comparison with fixed-based structures, which is more pronounced for the cases of elastic and low level of inelasticity.